Zakat al-mustaghallat for Malaysian landlords of residential properties - Hanudin Amin; Imran Mehboob Shaikh (Emerald, 2023)
Purpose – This study aims to examine the zakat al-mustaghallat acceptance index (ZAMAi) through the examination of its predictors identified in this work, including attitude, social influence, self-efficacy, amount of information and Islamic altruism, at best. Design/methodology/approach – Drawing from the attitude-social influence-self efficacy model, this study evaluated the effects of these factors on ZAMAi using an empirical investigation surveying 184 respondents who were identified as the owners of residential properties in Malaysia. Findings – In the core model, this study found significant outcomes for the effects of attitude, social influence, self-efficacy, amount of information and Islamic altruism, along with the demographic items tested. For post hoc analysis, this study found two significant outcomes drawn from the role of attitude as a mediating variable in this study. Research limitations/implications – The results obtained from this study should be used with caution owing to its limited applicability and the constraints of subjects and variables in the framework developed. Practical implications – The results obtained can become a yardstick to gauge the success of zakat al-mustaghallat acceptance in Malaysia. Originality/value – This study introduced new measures of ZAMAi, where Malaysian landlords are brought into play